Effects of Knee Joint Angle and Contraction Intensity on the Triceps Surae Stiffness - Lin, Ming; Deng, Weixin; Liang, Hongying; Yu, Suiqing; Xu, Qin; Liu, Chunlong (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Monitoring the contractility of muscles assists the clinician in understanding how muscle functions as part of the kinetic system. This study investigated the effect of knee joint angles under different resistance on the stiffness of the medial gastrocnemius (MG), lateral gastrocnemius (LG) and soleus (SOL) muscles using shear wave elastography (SWE) technique. Methods: Twenty-two females were recruited. During isometric plantar-flexion, at knee 0-degree (fully extended) and knee 90-degree (flexed 90°), the shear modulus on the MG, LG, and SOL were measured by shear wave elastography at no contraction and 2 intensities (40% and 80%) of maximal voluntary contraction (MVC), respectively. Shear modulus is a mechanical parameter to describe stiffness and stiffness is a proxy for muscle contractility. Results: There were moderate to high positive correlations between the active stiffness of triceps surae muscles and isometric contraction intensity (r: 0.57–0.91, p＜0.001). The active stiffness in MG and LG with extended knees were higher than that with flexed knees (p＜0.001). The active stiffness in SOL with flexed knee was higher than that with extended knee (p＜0.001). Conclusions: Active stiffness can be considered as a quantitative indicator generated by the force output of the triceps surae. Different knee joint angles cause three triceps surae muscles to exhibit non-uniform mechanical properties, which may explain part of the mechanism of soft tissue injury during physical exercise.